«Those Precious Memories». Biographies in El Álbum Mexicano (1849): portraits for a national imaginary - Ferrús Antón, Beatriz (2023)
El Álbum Mexicano was one of the publishing enterprises of the famous printer Ignacio Cumplido. The young Mexican republic needed to create an account of itself and its citizens and found a privileged space in the illustrated press. Biographies of characters, descriptions of monuments and landscapes, texts on customs, etc., sought to create a collection of images that would allow the readers of the publication to think of themselves as part of a national unity. This article analyses the importance of the biographies that appeared in the newspaper, a genre of great importance for presenting models of citizenship, masculinity and femininity that would serve as a social model.